Psychological well-being impacts among university students on online learning during the COVID-19 pandemic - Nor Shafrin Ahmad; Aziah Ismail; Zuhda Husain (International Journal of Public Health Science (IJPHS), 2022)
During the COVID-19 pandemic, universities in Malaysia implemented online learning. This long-time remote learning is very challenging to some university students. The purpose of this study was to identify the effect of psychological well-being on depression, anxiety, and stress of university students on online learning during the COVID-19 pandemic. The quantitative data were collected from 325 students from a university in the northern part of Peninsular Malaysia. The survey was conducted online through Google Forms. Two instruments used were Depression, Anxiety, Stress Scale (DASS-21) and the psychological well-being scale (PWBS-8). The data were analyzed using descriptive and inferential methods. The study found that 34.9% of the students were depressed, 60.9% anxious, and 32% stressed. The study found that 23% of the variability in psychological well-being (PWB) affected university students’ depression, anxiety, and stress. This finding demonstrates the magnitude of burden that university students now bear during online learning. Therefore, higher education institutions can play a fundamental role in assisting students to cope with their depression, anxiety, and stress. Authorities should also prioritize determining appropriate student facilities and resources. Structured programmes for distress reduction and blended learning are suggested for use in teaching and learning.